2002
DOI: 10.1017/s0950268802007793
|View full text |Cite
|
Sign up to set email alerts
|

The role of solar ultraviolet irradiation in zoster

Abstract: Ultraviolet radiation (UVR) suppresses many aspects of cell-mediated immunity but it is uncertain whether solar UV exposure alters resistance to human infectious diseases. Varicella-zoster virus (VZV) causes varicella (chickenpox) and can reactivate from latency to cause zoster (shingles). The monthly incidence of chickenpox and zoster in a defined Polish population over 2 years was recorded and ground level solar UV was measured daily. There was a significant seasonality of UVR. Evidence of seasonal variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 14 publications
2
57
1
3
Order By: Relevance
“…30 Moreover, additional sunny hours may increase exposure to UV irradiation, which may act as an immunosuppressant and reduce immunity to VZV. 31 …”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, additional sunny hours may increase exposure to UV irradiation, which may act as an immunosuppressant and reduce immunity to VZV. 31 …”
Section: Discussionmentioning
confidence: 99%
“…araflt›rmalar›nda herpes zosterin erkeklerde daha s›k görüldü¤ünü, bafl ve yüz gibi güne-fle daha s›k maruz kalan alanlarda, günefl ›fl›nlar› ile hastal›¤›n ortaya ç›kmas› aras›ndaki anlaml› mevsimsel iliflkiyi tespit etmifller ve hastal›¤›n temmuz ve a¤ustos aylar›nda pik yapt›¤›-n› vurgulam›fllard›r. Herpes zosterin yaz dönemleri insidans›ndaki art›fl› da UV radyasyonun hücresel immünitede yapt›-¤› supresyona ba¤lam›fllard›r 21 .Çelik ve ark. herpes zosteri sonbahar mevsiminde %32 oran›nda tespit etmifller, di¤er üç mevsim aras›nda fark görememifllerdir 22 .…”
Section: Tart›flmaunclassified
“…Previous reports evaluating the seasonality of varicella and its association with meteorologic factors have analyzed either simple correlations or only a few meteorologic factors, which could lead to inaccurate conclusions [12,17]. In our study, when simple correlations were obtained, four out of the seven meteorologic factors studied had a positive correlation with varicella epidemics.…”
Section: Discussionmentioning
confidence: 55%
“…Animal and human studies have demonstrated the immunosuppression caused by UV radiation and its effects in the reactivation of herpes simplex virus (HSV), human immunodeficiency virus (HIV) replication, or human papillomavirus (HPV)-triggered skin cancer [26]. In herpes zoster disease, although most of the cases show no seasonality, there are some reports of a summer predominance [17,27], suggesting an effect of UV radiation on the reactivation of VZV and local and systemic cell-mediated immunosuppression [26]. One of the most remarkable findings in our study was a positive correlation between solar radiation and the number of cases of varicella infection.…”
Section: Discussionmentioning
confidence: 99%